THE ROLE OF CRITICAL DIGITAL LITERACY IN FOREIGN LANGUAGE LEARNING: A SURVEY ON YOUNG LEARNERS - Muhamad Laudy Armanda; Rolisda Yosintha (ETERNAL (English, Teaching, Learning and Research Journal), 2022)
The covid-19 pandemic has brought influential disruptions to the education sector. EFL teachers ought to find ways to trigger their learners by utilizing ICT. Digital literacy tools which it possible for young learners to improve their understanding of every word, text, and meaning conveyed. There will be new risks and threats that can only be countered with adequate digital literacy knowledge in all-digital situations. Young learners are indicated as Gen-Z, which might be digital natives. Thus, this study aims to survey EFL teacher and learners in digital literacy at the level of young learners, focusing on the critical digital literacy skills in a rural school. To obtain the data, the authors used questionnaires and some interviews. To assess the young learners’ view, the authors tracked it of 31 EFL learners by using questionnaires. While the interview is used to the EFL teacher’ view. Evidences show the role of critical digital literacy is considered it an effective ability to be acquired in learning English, and it can increase the young learners’ motivation because in learning English using technology is easier and more enjoyable.